Edmodo-Based Mathematical Learning Analysis - Rahmi Rahmi; Putri Yulia; Rahmi Putri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The number of students who do not participate in the online mathematics learning process makes it difficult for teachers to control students and it is also difficult to create discipline. This study aims to describe: planning, implementation, evaluation, the obstacles that hinder the learning of mathematics using Edmodo. The approach and type of research used is a qualitative method with the type of research being grounded theory. The research subjects were teachers and students of class VIII SMP N 7 Sungai Penuh. Data collection techniques using observation, interviews and documentation. The data obtained were analyzed through data reduction, data display, and drawing conclusions. The results of this study are 1) the planning of the use of media was successfully implemented by the teacher., 2) the implementation of the use of the Edmodo learning media was coherent starting from the preliminary stage, the core stage and the closing stage., 3) the evaluation was carried out to the maximum, because the teacher could monitor student performance in the learning process through edmodo media during the learning process takes place and students are also on time in collecting assignments, there are even no more students who do not collect assignments., 4) and the obstacles that hinder e-learning learning using edmodo in learning mathematics, such as the internet network and also the lack of supervision from parents of students.